Ekoterapi dalam perspektif Islam: Analisis terhadap teks-teks al-Quran - Dzulfaidhi Hakimie Dzulraidi; Mohd Solleh Ab Razak; Umar Muhammad Noor; Mohd Dahlan A Malek (Researchgate, 2024)
Ecotherapy, a therapeutic approach involving the natural environment, has gained popularity in modern medicine as a method for supporting mental well-being. However, comprehensive research linking ecotherapy with Islamic teachings is limited, particularly in analyzing revelatory texts that potentially align with ecotherapy principles. The primary issue of this study is the lack of references examining Islamic revelations as guidance for modern nature-based therapies. This study is crucial for enhancing understanding of the compatibility between ecotherapy and Islamic values, as well as introducing a culturally relevant therapeutic alternative for the Muslim community. Using qualitative methodology, this study involves textual analysis of Quranic verses and hadiths that touch upon aspects of nature and reflective practices like tafakkur (contemplation) and tadabbur (reflection). Content analysis is employed to identify ecotherapy principles embedded within revelatory texts and how these elements contribute to mental and spiritual well-being. The study finds that modern ecotherapy concepts align with Islamic values that encourage human interaction with nature as a medium for reflection and inner peace. This includes the practice of tafakkur on nature, as encouraged in the Quran, as well as the Prophet’s (SAW) experiences in nature for inner tranquility. This study suggests that revelation-based ecotherapy can offer a holistic mental care model suitable for Muslims. Further studies are recommended to explore the application of Islamic ecotherapy in modern contexts, such as the role of specific natural elements, like water and plants, to enrich nature-based therapeutic concepts within the Islamic tradition.